FROM THE HISTORY OF THE ACTIVITIES OF THE N. A. SEMASHKO INSTITUTE FOR TRAINING SPECIALISTS IN PHYSIOTHERAPY AND SANATORIUM TREATMENT IN UZBEKISTAN - Rashidakhan Muqimovna Akhmedova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the history of the N. A. Semashko Institute in training specialists in physiotherapy and sanatorium-resort therapy, it includes the work carried out by the institute to provide sanatoriums with specialist personnel, shortcomings in the provision of personnel to sanatoriums in the republic, existing problems and the history of achievements in this area analyzed on the basis of archival materials.